Effect of pemafibrate on liver enzymes and shear wave velocity in non-alcoholic fatty liver disease patients - Sugimoto, Ryosuke; Iwasa, Motoh; Eguchi, Akiko; Tamai, Yasuyuki; Shigefuku, Ryuta; Fujiwara, Naoto; Tanaka, Hideaki; Kobayashi, Yoshinao; Ikoma, Jiro; Kaito, Masahiko; Nakagawa, Hayato (Frontiers in Medicine, 2023)
Background/Aims Pemafibrate is a selective peroxisome proliferator-activated receptor α modulator that improves serum alanine aminotransferase (ALT) in dyslipidemia patients. Pemafibrate was reported to reduce ALT in non-alcoholic fatty liver disease (NAFLD) patients, but efficacy was not clearly elucidated due to the small size of previous study populations. Therefore, we explored pemafibrate efficacy in NAFLD patients. Methods We retrospectively evaluated pemafibrate efficacy on liver enzymes (n = 132) and liver shear wave velocity (SWV, n = 51) in NAFLD patients who had taken pemafibrate for at least 24 weeks. Results Patient ALT levels were decreased from 81.0 IU/L at baseline to 48.0 IU/L at week 24 (P < 0.0001). Serum levels of aspartate aminotransferase (AST), γ-glutamyl transpeptidase (γ-GTP) and triglyceride (TG) were significantly decreased, and high-density lipoprotein cholesterol and platelet count were significantly increased, with no change in body weight being observed. Study participant SWV values decreased from 1.45 m/s at baseline to 1.32 m/s at week 48 (P < 0.001). Older age (P = 0.035) and serum TG levels (P = 0.048) were significantly associated with normalized ALT. Changes in AST, ALT, γ-GTP and body weight were significantly correlated with change in SWV. Conclusion Pemafibrate significantly improves liver function, serum TG and liver stiffness in NAFLD patients. Pemafibrate is a promising therapeutic agent for NAFLD and may be a candidate for NAFLD patients with elevated TG.